Use of over-the-country derivatives to protect construction enterprises from price and sales risks caused by economic cyclicality (using the example of the aerated concrete market) - SKRYPNYK, Olga; SKRYPNYK, Andriy (Ways to Improve Construction Efficiency, 2025)
The article examines the issue of protecting construction enterprises from price and sales risks caused by economic cyclicality (using the example of the aerated concrete market) using financial derivatives (forwards, futures and options), which is extremely important, especially during economic crises. Given that in Ukrainian economic science, the issues of specific mechanisms for protecting against the risks of price increases in construction are practically not covered, and existing works on hedging and derivatives do not take into account industry specifics, this article aims to fill this gap. The purpose of the study is to substantiate the feasibility and develop mechanisms for using derivative instruments, in particular over-the-counter futures contracts, to hedge price risks of price increases for construction products and to ensure that construction enterprises have guaranteed sales of products not yet manufactured. To achieve the goal, methods of analysis, comparison, economic and mathematical modeling, as well as a systematic approach were used, which allowed adapting financial instruments traditionally used in the stock and commodity markets to the specific conditions of the construction sector. The study shows that since construction does not belong to the industries that consume exchange-traded raw materials, the use of exchange-traded derivatives to hedge price risks for building materials is impossible. Therefore, the hedging system proposed by the author is based on the preliminary sale of building materials using over-the-counter derivatives, with the help of which the developer can reserve the required volume of building goods at a fixed price, paying an advance payment that serves as a guarantee deposit. This allows the developer to fix costs, and the enterprise to receive working capital and confidence in the sale of products that have not yet been manufactured. The article also derives formulas for determining the equilibrium amount of the advance payment under a futures contract, which allows you to regulate sales volumes and, if necessary, refuse bank loans. The possibility of using European-type CALL options, which may be attractive to buyers who are not ready to pay a significant advance, is also considered. Calculations on the example of the aerated concrete market have shown that the equilibrium value of options is approximately three times less than the advance payment under a futures contract. The article presents the conditions necessary for the functioning of the OTC derivatives trading system, such as product homogeneity, a significant number of buyers, a steady trend of price growth, and provision of real goods. In addition, the article considers options for creating a trading system for these derivatives and highlights the conditions necessary for this. The results of the study show that the use of derivative financial instruments makes it possible to reduce the negative impact of cyclical fluctuations in the economy on the financial stability of construction enterprises, and also increases the predictability of their costs and revenues at different phases of the economic cycle.